Nonprofit Neighborhoods: An Urban History of Inequality and the American State, By Claire Dunning, The University of Chicago Press, 2022 - Emily I. Nwakpuda (Journal of Social Equity and Public Administration)
Dunning's (2022) conceptualization of nonprofit neighborhoods is a rebuke to the idea of the independent third sector in which private neighborhood nonprofits evolve as a unit of governance that structurally embeds nonprofits into the issue of urban crisis and the democratic process through their partnerships with government and other funders. Using the case of Boston, the author informs readers that the government-nonprofit partnerships fueled by grants, contracts, and loans within the framework of nonprofit neighborhoods maintains and advances racism and inequity in America. The author defends this proposition by leveraging a historical lens, archival data, and autobiographical descriptions to magnify readers' attention on the racially biased treatment of leaders, workers, and community members associated with nonprofit neighborhoods among diverse communities. Nonprofit Neighborhoods concludes with several exciting future research directions to help deepen our understanding of nonprofit neighborhoods as a necessity and a liability to social equity.